Is dental evaluation considered in unilateral maxillary sinusitis? A retrospective case series. (17th November 2018) - Ly, Don; Hellgren, Johan
Abstract: Objective: Are patients with symptomatic unilateral maxillary sinusitis sent for a dental evaluation of odontogenic maxillary sinusitis (OMS)? Patients and methods: The medical records of all patients diagnosed with sinusitis at a university Ear-nose and throat (ENT) clinic from 2010 to 2015 were scrutinized for symptomatic unilateral maxillary sinusitis verified on CT. Any dental evaluation was recorded, as well as symptoms of OMS, duration to dental evaluation, diagnosis of OMS and dental treatment. Results: A total of 1338 patients diagnosed with sinusitis were screened; 172 had unilateral maxillary sinusitis and 48% (82/172) OMS. 34% did not have any dental evaluation at all. Patients referred to local specialist dental care waited a median of 11 weeks for evaluation and a median of 15 weeks further for dental treatment. Symptoms more frequently reported in OMS patients were foul smell or taste (43.9% vs 11.1%, p < .0001), purulent rhinorrhea (40% vs 19.1%, p = .015) than non-OMS patients. The OMS group also reported more frequently that they were active smokers (31.7% vs 10%, p = .0005). Conclusions: OMS was found in 48% of unilateral maxillary sinusitis and one-third of the patients with unilateral maxillary sinusitis had no dental evaluation. Low awareness of OMS could delay diagnosis and treatment.